The Effect of The Sage Circle Strategy on Reading Comprehension Among Second-Grade Middle School Students (Journal of the College of Basic Education, 2025)
This study appears to be a thorough and well-structured investigation into the impact of the Wise Judgment Circle strategy on reading comprehension for second intermediate grade female students. The approach you've described, involving an experimental group and a control group, is ideal for assessing the effectiveness of an educational strategy like this one. Summary of Key Elements:Objective To examine the effect of the Wise Judgment Circle strategy on reading comprehension among female students in the second intermediate grade. - There is no significant difference in reading comprehension test scores between students using the Wise Judgment Circle strategy and those using traditional methods.Research Design - Experimental Design - Random assignment of students to experimental and control groups. - Pre-test and post-test to measure changes in reading comprehension. -Partial Control Design: This design allows for some level of control over extraneous variables while allowing natural group dynamics to unfold.Sample - 60 second intermediate grade female students from schools in Rusafa First, Baghdad. - Randomly divided into two groups: experimental (30 students) and control (30 students).Equivalence of Groups - Ensured equivalence in variables such as age, prior academic achievement, intelligence (measured by Raven’s Progressive Matrices), and pre-test reading comprehension scores.Controlled Variables - Scientific material: Nine specific topics from the Arabic language textbook for the second semester of the academic year 2024–2025. - Extraneous Variables: Controlled to avoid any external factors that could influence the results.